Overview of the EDEN ISS Project: Design and Operation of an Antarctic greenhouse - Vrakking, Vincent (2019)
This presentation detailed the design and operation of a closed-loop greenhouse in a space-analogue environment in the Antarctic, as carried out in the EDEN ISS Project.